Promoting more socially responsible corporations through a corporate law regulatory framework. (2nd January 2018) - Zhao, Jingchen
Abstract : This paper aims to lay the foundations for a more critical approach to the relationship between corporate social responsibility (CSR) and corporate law. Limitations on legislative approaches including directors' duties, disclosure of information, sustainable decisions, direct promotion and corporate internal management structure are critically analysed, trying to find well thought-out and effectively implemented adjudication that provides meaningful instruction for regulating CSR. The paper explores the manner in which corporate law may contribute to accommodating CSR principles within corporate strategies, in order to establish a transformative legal regulatory framework within corporate law by using the authoritative legal mode to promote corporate regulatory mechanisms. The paper critically studies a few legislative measures supported by the relevant legislative experiences from various jurisdictions as examples of currently enforced CSR laws at national level, in order to offer comprehensive and potentially effective legislative suggestions for accommodating CSR elements. However, a 'one size fits all' approach is clearly not desirable, and these suggestions should be interpreted and implemented in a locally relevant manner, according to path dependence theory.